Probing Electronic Symmetry Reduction during Charge Migration via Time‐Resolved X‐Ray Diffraction. Issue 2 (11th November 2022) - Tremblay, Jean Christophe; Blanc, Ambre; Krause, Pascal; Giri, Sucharita; Dixit, Gopal
Abstract: The present work focuses on probing ultrafast charge migration after symmetry‐breaking excitation using ultrashort laser pulses. LiCN is chosen as prototypical system because it can be oriented in the laboratory frame and it possesses optically‐accessible charge transfer states at low energies. The charge migration is simulated within the hybrid time‐dependent density functional theory/configuration interaction framework. Time‐resolved electronic current densities and simulated time‐resolved x‐ray diffraction signals are used to unravel the mechanism of charge migration. Our simulations demonstrate that specific choices of laser polarization lead to a control over the symmetry of the induced charge migration. Moreover, time‐resolved x‐ray diffraction signals are shown to encode transient symmetry reduction at intermediate times. Abstract : Charge migration induced by ultrashort laser pulses generally reduces the electronic symmetry in a molecular system. Many‐electron dynamics simulations demonstrate that specific choices of laser polarizations affects the symmetries of the charge migration. Because time‐resolved x‐ray diffraction signals is sensitive to the phase of the wave packet, this has consequences on the symmetry of the probed signal.